Examining English learning materials based on genre-based approach for vocational high school students - Hesti Widyasari (Journal of English Language and Pedagogy, 2021)
Abstract The aims of this study were (1) to examine English learning materials based on genre-based approach (GBA) for the eleventh-graders of Fashion Design department at Vocational High Schools and (2) to reveal the efficacy of the developed learning materials in developing the students’ English skills. Data collection used observation and interview. Data were analyzed qualitatively upon the observation and interview. The subjects of this study were the English teacher and 14 students of eleventh-graders from SMK Muhammadiyah Gamping, Sleman, Indonesia. The findings showed that description of examining two units of materials consisted of building knowledge of field (BKoF), modelling of text (MoT), joint construction of text (JCoT),  and independent construction of text (ICoT) stages. In BKoF stage, students warmed up the topics by discussing some questions, next, in MoT stage, students gained model text input from listening and reading tasks, then, in JCoT stage, students practiced speaking and writing collaboratively in groups, after that in ICoT stage, students practiced speaking and writing individually. Meanwhile, the efficacy of the developed materials the students participated actively during the try-out and achieved mean score of 4.18 (good category). It could be concluded that the developed materials were appropriate to be implemented for tenth-graders’ English learning of Fashion Design department. This was consistent with students’ activities in classroom performance they were engaged in the teaching and learning process and produce the learning outcomes. Keywords: English learning materials, genre-based approach, tenth-graders’ efficiacy